Hybrid learning. theory and practice : 7th International Conference, ICHL 2014, Shanghai, China, August 8-10, 2014. Proceedings - Fong, Joseph; Zhang, Jiping; Kwan, Reggie; Kwok, Lam For; Cheung, Simon K. S. (Lecture Notes in Computer Science, 2014)
This book constitutes the refereed proceedings of the 7th International Conference on Hybrid Learning, ICHL 2014, held in Shanghai, China, in August 2014. The 31 papers presented were carefully reviewed and selected from 90 submissions. The selected papers cover various aspects on hybrid learning, computer supported collaborative learning, expericiences in hybrid learning, improved flexibility on learning processes, and the pedagogical and psychological issues of hybrid learning.